Psychometric Properties of the Short Forms of the Social Interaction Anxiety Scale and the Social Phobia Scale in a Chinese College Sample - Ouyang, Xueyuan; Cai, Yan; Tu, Dongbo (Frontiers in Psychology, 2020)
This study was carried out to examine the factor structure and psychometric properties of the Social Interaction Anxiety Scale (SIAS) and Social Phobia Scale (SPS) in a sample of 1,001 Chinese college students (male: 34%; female: 66%). Confirmatory factor analysis (CFA) indicated that the two-factor of shorten version SIAS-6/SPS-6 fitted the data well. In addition, the item response theory (IRT) method confirmed the construct and items for the 12-item of SIAS-6/SPS-6 with satisfactory discrimination, threshold parameters, and test information curve. It is concluded that the factor structure and the psychometric properties of the SIAS-6/SPS-6 support the use of the scales for assessment in Chinese college sample.